AIEgen‐enhanced protein imaging: Probe design and sensing mechanisms. Issue 3 (8th March 2021) - Naghibi, Sanaz; Chen, Tong; Jamshidi Ghahfarokhi, Amin; Tang, Youhong
Abstract: Proteins are the building blocks of life, regarded as one of the most complex and crucial biomacromolecules in biological systems, and playing a significant role in executing genes and transferring genetic information. According to recent research, due to the structural intricacy of proteins and their sensitivity to physical and chemical degradation processes, they could be utilized as biomarkers or therapeutic agents in the diagnosis, treatment, or even prevention of different diseases. Therefore, modern pathways have been developed for understanding the function of proteins, resulting in intriguing approaches in the field of protein‐related diseases. The diagnostic strategies to deal with such diseases, including protein analysis, protein quantification, and protein imaging, were argued in depth. Meanwhile, the aggregation‐induced emission (AIE) concept and its potential applications for real‐time imaging make AIE luminogens (AIEgen) attractive for protein imaging. In general, AIEgens refer to those luminogenic chemicals that are nonluminescent in solution, but luminescent in either the aggregated or solid states. This review is focused on the emergence of AIE materials in protein tracking, detecting, and imaging for medical applications. Abstract : The performance of the AIE concept applied to the existed protein imaging is reviewed by focusing on the functions of AIE biomarkers in the tracking, detecting, and real‐time monitoring of protein‐related diseases. For this aim, 13 groups of proteins are screened, the theoretical principles of probe designing, and the mechanisms of their detection are discussed in depth.